Ciputra Tjipoetra [Indonesia, Chairman of Ciputra Business Group] - Tjipoetra, Ciputra (Institutional Knowledge at Singapore Management University, 2015)
Ciputra is the Founder and Chairman of Ciputra Business Group, an Indonesian property conglomerate. He tells DNA how he worked and navigated his way through Indonesia's political and business scene to build his business empire and shares his thoughts on entrepreneurship and leadership.